Detection of Antibiotic Residues in Blossom Honeys from Different Regions in Turkey by LC-MS/MS Method - Buket Er Demirhan; Burak Demirhan (MDPI AG, 2022)
In the present study, a total of 80 commercial blossom honey samples were obtained from local markets in Ankara, Turkey. These honeys were analyzed for 35 important and risky antibiotics (sulfonamide, tetracycline, macrolide, cephalosporin, aminoglycoside, quinolone, nitrofuran, chloramphenicol, and anthelmintic groups) by the LC-MS/MS multi-antibiotic method. In addition to these analyses, pH measure, moisture, and electrical conductivity were determined in these honey samples. Finally, seven out of 35 antibiotic residues investigated in the honeys were positive. The most frequently detected antibiotics in the analyzed samples were dihydrostreptomycin, streptomycin, erythromycin, sulfadimidine (sulfamethazine), and enrofloxacin as 58.75%, 22.5%, 13.75%, 10%, and 2.5%, respectively. Tetracycline and doxycycline were detected in only one sample. The pH, moisture, and electrical conductivity values of the honey samples were determined as between pH 3.78 and 5.41, 17.48 and 18.03%, and 0.25 and 0.47 mS/cm, respectively. In terms of food safety and human health, it is very important to monitor the residues of these pharmacologically active substances with analytical methods.